Autonomous cooling system with Solar Energy - Gutiérrez Valderrama, Jhorman J.
Among the renewable energy sources, solar photovoltaic (PV) systems represent an alternative to conventional sources, such as hydro or wind which involve high costs in the processes of generation and distribution of energy produced, and also cost overrun for maintenance of electrical networks and a greater environmental impact throughout the process.(Tobajas, 2012).Sometimes, Photovoltaic systems are inefficient because of miscalculations in the power required and improper selection of the electrical components that generate this power. Usually it is working with a higher percentage of the power required by the system, considering the existing variation in environmental factors in the operating place such as temperature and brightness. This range of safety power represents a cost overrun which must be assumed to ensure the proper functioning of the system.This research raises the design and construction of a system of autonomous and portable cooling dedicated to the preservation and securing of the cold chain in perishable foods. It will be designed a load control which permanently monitors the level of voltage and current in both the battery and on the panels. By the time the energy level reaches the battery from the panels is not enough, it automatically connects to the commercial network guaranteeing the proper operation. This system allows to work with the rated power required avoiding excessive power and therefore a decrease in costs.